Answer:
p = - 11x
q = - 6y + 3
r = 3z
s = - 15x + y
t = 2x - 14z - 11
u = 9y + 3x - 14
Explanation:
Let, 7x + p + 3 - 9 = - 4x - 6
⇒ p = - 4x - 6 - 7x + 9 - 3
⇒ p = - 11x (Answer)
Let, - 19y + q + 15 = - 25y + 18
⇒ q = - 25y + 19y + 18 - 15
⇒ q = - 6y + 3 (Answer)
Let, - 7z + r - z + 14 = - 5z + 14
⇒ r = - 5z + 7z + z = 3z (Answer)
Let, 4x - 11y + s = - 11x - 10y
⇒ s = - 11x - 4x - 10y + 11y
⇒ s = - 15x + y (Answer)
Let, - 25x + z + t = - 23x - 13z - 11
⇒ t = - 23x + 25x - 13z - z - 11
⇒ t = 2x - 14z - 11 (Answer)
Let, 7y + u - 18 = 16y + 3x - 32
⇒ u = 16y - 7y + 3x - 32 + 18
⇒ u = 9y + 3x - 14 (Answer)